1982
DOI: 10.1080/03015521.1982.10427876
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ‘Grasslands Matua’ prairie grass and ‘Grasslands Maru’ phalaris with and without lucerne in Canterbury

Abstract: Mixtures of Matua prame grass and Maru phalaris with Saranac lucerne, grown on silt loam and cut infrequently, were compared with pure sowings of lucerne, Matua, Maru, and 'Grasslands Nui' ryegrass. Major nutrients returned in fertiliser mixture were equivalent to their content in the cut herbage. Of the mixtures, Matua yielded the most dry matter (DM) over 2 years (19000-224000 kglha/a, cf. 18500-19500 kglha/a for pure lucerne). Pure swards of Matua and Maru yielded more than Nui in all seasons, highest annua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

1983
1983
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 6 publications
0
10
1
Order By: Relevance
“…Prairie grass is another potential alternative for the dairy pastures of southern Australia, as it is characterized by high summer growth, drought‐tolerance, insect‐tolerance and high preference by ruminant livestock (Fraser, 1982; DeLacy, 1987). Vartha (1977) reported that dry‐matter (DM) utilization of prairie grass was 0·53 greater than that of ryegrass (13·2 vs. 8·6 t DM h a −1 ) in a dryland study on the South Island of New Zealand, largely because of the greater productivity of prairie grass over the summer months.…”
Section: Introductionmentioning
confidence: 99%
“…Prairie grass is another potential alternative for the dairy pastures of southern Australia, as it is characterized by high summer growth, drought‐tolerance, insect‐tolerance and high preference by ruminant livestock (Fraser, 1982; DeLacy, 1987). Vartha (1977) reported that dry‐matter (DM) utilization of prairie grass was 0·53 greater than that of ryegrass (13·2 vs. 8·6 t DM h a −1 ) in a dryland study on the South Island of New Zealand, largely because of the greater productivity of prairie grass over the summer months.…”
Section: Introductionmentioning
confidence: 99%
“…1, Grasslands Division, DSIR 1982). Its cool-season growth was better than other perennial grasses (Fraser 1982) and has compared well with annual and biennial ryegrasses (Lalium multiflorum Lam.) (Wilson 1977).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the other predominantly dairy areas of Taranaki or Northland it was little used despite it being wellknown. Well publicised research in Canterbury (Fraser 1982(Fraser , 1983, demonstrating the great potential of Matua in sheep systems has not encouraged sheep farmers to use it However,Matua, is much used in Canterburypossiblybecause theresearchwas done thereand becauseof the region's rapidlyexpanding dairying sector (parker 1985).Prairie grass occurs naturally indry, fertileenvironments(RumbalI1973); persistenceis poor in heavywet soils (Lancashireet al 1980) which are common in high rainfall areas. Thisfactormaybe a reasonfor thelowuse ofMatua in high rainfall areas such as Northland,Taranaki, Westland,and Southland.…”
Section: Ryegrassmentioning
confidence: 97%
“…Significant advantages havebeen demonstrated fromusingimproved cultivarsofalternative species to perennial ryegrass, e.g., the superiority of 'GrasslandsRoa' tallfescue(Festuca arundinacea) on peat soils in theWaikato(Goold& Van der Elst 1980) .and 'GrasslandsMatua'prairiegrass(Bromus willdenowil)inCanterbury (Fraser 1982(Fraser , 1983(Fraser ,1985 intermsofpastureandanimalproduction. However, their effect has been small and Lancashire (1985) suggestedlowandfluctuating volumes of seed,high seed prices, and unfavourable opinions generated aboutthespeciesasfactors thatcouldaccountforthe slow uptakeof new alternative species.…”
Section: Introductionmentioning
confidence: 98%